The Impact Of The Level Of The Intestinal Short Chain Fatty Acids In Inflammatory Bowel Disease Patients Versus Healthy Subjects - Huda-Faujan, N.; A.S. Abdulamir; A.B. Fatimah; O. Muhammad Anas; M. Shuhaimi; A.M. Yazid; Y.Y. Loong (Bentham Science Publishers, 2024)
Non-Indexed Publication